Analysis of waste generation characteristics as a reference for TPS 3R planning in community-based waste management efforts - Aprilia, Reza; Noerhayati, Eko; Rahmawati, Anita (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Waste management is a critical issue in Indonesia, particularly in rural areas like Pandansari Lor Village in Malang Regency. Improper waste disposal practices, such as open burning and dumping in rivers, pose environmental and health hazards. This study aims to analyze the waste generation characteristics in Pandansari Lor Village as a baseline for planning a community-based Reduce, Reuse, Recycl waste processing site/Tempat Pengolahan Sampah Reduce, Reuse, Recycle (TPS 3R). Method: A waste sampling method was conducted following the SNI 19-3964-1994 guidelines to measure the waste generation rate, density, and composition. Findings: Household waste data analysis shows that low-income households generate 39.1% of the total waste, while middle and high income households contribute 28.7% and 32.2%, respectively. The amount of waste per day was recorded at 9.73 kg on Friday for low income households, while for middle and high income households, the highest amount of waste occurred on Monday with 8.56 kg and 9.09 kg, respectively. Conclusion: These findings indicate fluctuations in waste generation patterns based on income levels, with certain days producing larger amounts of waste. Novelty/Originality of this article: This study proposes a 3R TPS model adapted to rural waste, focusing on organic waste composting and plastic recycling. This model is designed to increase community participation in waste management through community-based education and empowerment.